Pastoral da Criança: uma prática politico-educativa não-formal - Barbosa, Sueli Aparecida Bertol (2008)
Teaching practices integrate the universe of social practices and are part of all human groups. Pedagogy is focused on school teaching practices. However, school is not the only field of pedagogical action and investigation and researching every locus of pedagogical action broadens educational studies. This work investigates the Pastoral da Criança (PCç) social practice as political and teaching practice as well. PCç is an organ of social action which belongs to the Brazil Bishops National Conference (CNBB) and assists poor comunities, through voluntary work, instructing such comunities about health, nutrition, education and citizenship. The theory is based on concepts of non-formal education by Afonso (1989), Gohn (2001) and Libâneo (2007) and the Freirean Pedagogy. Regarding Freire's pedagogy the focus was on the analysis of dialogue categories, solidarity, awareness, oppressor, oppresed, oppression, banking education and problematizing education. The critics presented by Montaño (2003) regarding the role of State and ONGs (non-governmental organizations) in public policies guided the reflection about the PCç as public policy. Investigation comprised documental-bibliographic research of books, dissertations and thesis as well as field researh developed in Ponta Grossa Diocese. The methodology was based on Macedo (2000), mainly the Etnopesquisa Crítica e Multirreferencial nas Ciências Humanas e na Educação (Critical and Multirreferential ethnoresearch in Human Sciences and Education). Open and semistructured interviews, as well as photos, video recording and observation with field diary recording were used as data collection tools. The aim of this research was to systematize the elements which are part of the Pastoral da Criança pedagogical proposal. Finally, this work presents a possible systematization of Pastoral da Criança Pedagogy, concludes that in the socio-educational practice of PCç Freire's Pedagogy appears between recreation and adaptation and considers the PCç as part of social public policies.